ANALISIS KUALITAS LAYANAN PROGRAM TRANSPORTASI PUBLIK BUS TRANS JATIM PADA KORIDOR 1 JURUSAN SIDOARJO-SURABAYA-GRESIK - Abdul Aziz Hadi; Ari Subowo (Journal of Management and Public Policy, 2026)
Public transportation is a form of public service that plays a strategic role in supporting community mobility and facilitating social and economic activities in urban areas. The Government of East Java Province, through the Trans Jatim Bus program, seeks to provide safe, affordable, and integrated mass transportation services, particularly on Corridor 1 serving the Sidoarjo–Surabaya–Gresik route, which functions as a major mobility corridor within the Gerbangkertosusila metropolitan area. However, various issues related to service quality remain evident in its implementation, including passenger overcrowding during peak hours, punctuality problems, staff professionalism, and limited facilities that are accessible to persons with disabilities. This study aims to analyze the service quality of the Trans Jatim Bus on Corridor 1 from the perspective of public service quality and to identify factors influencing service performance. The research employs a qualitative approach using a descriptive method. Data were collected through interviews, observations, and documentation studies involving service users, operational staff, and officials from the East Java Provincial Transportation Agency. The findings indicate that the overall service quality of the Trans Jatim Bus on Corridor 1 is relatively good, particularly in terms of fare affordability and fleet availability. Nevertheless, several service quality dimensions remain suboptimal, especially reliability, responsiveness, and empathy, as reflected in passenger overcrowding, limited bus stop facilities, and inadequate accessibility for vulnerable groups. Factors influencing service quality include staff competence, the availability of facilities and infrastructure, and the effectiveness of operational management. This study is expected to serve as an evaluation reference for local governments in improving inclusive and sustainable public transportation services.